Fios que tecem a formação profissional: um estudo sobre o estágio supervisionado nos cursos de Serviço Social da Regional Sul I da Associação Brasileira de Ensino e Pesquisa em Serviço Social (ABEPSS) - Albiero, Cleci Elisa (2021)
This thesis aims to discuss professional education in Social Work from the perspective of supervised internship and the economic, political, and social determinants that affect the context of commodification in education policy, permeated by a neoliberal political agenda. It starts with concerns and questions arising from the experience as a professor and researcher in the area of professional education in Social Work. As a research method, it was used the qualitative method with quantitative data, based on the assumptions of critical social theory and theorists in the area of knowledge of Social Work and Social Sciences, articulating them to exploratory and descriptive research, through theoretical-bibliographic, documentary, and field research. The field research was carried out with internship teacher coordinators and students in their last year of formation in Social Work from six (6) Social Work courses in the Regional Sul I of ABEPSS in the face-to-face modality of public and private education, in the states of Rio Grande do Sul, Santa Catarina, and Paraná. For the field research, a semi-structured interview was used with the internship teacher coordinators of the 06 courses to know the internship proposal of the teaching unit, how it is organized and if it aligns with the ABEPSS curricular guidelines, with the national internship policy, and the resolutions and regulations in force. Concerning the students, a semi-structured questionnaire was used to know their perception regarding internship and professional education and map the socio-occupational spaces, places of the supervised internship. The approximations with the teachers point to significant advances in neoliberal policy in the field of education, especially in higher education, as well as exposing the vertiginous advancement of private education and formation in the distance modality, causing changes in the concept of professional education, impacts on the profession and the discredit and precariousness of the teacher's work. The investigation concerning the supervised internship process, from the students' perspective, points to the dismantling of the education policy, the conservatism steeped in a declared neo-conservatism and experienced by them in the internship spaces, relegating professional work and social policy to welfare, as well as to the overwhelming wave of science and research denial, driven by a technological, bureaucratic and immediate nature of professional education. Finally, all these elements analyzed throughout this thesis have contributed to reflections on significant changes and impacts on professional education, changes, and theoretical-methodological weaknesses in the pedagogical process and the constitutive dimensions of the profession